THE OIL MARKET FROM THE MONOPOLY OF PRODUCERS TO THE MONOPOLY OF CONSUMERS - Dr .Esam Hadi Mohammed; Najah Hawar Saeed Al-bazzaz (Scholar Express Journals, 2022)
The oil market is characterized by several characteristics that make the oil market different from the rest of the markets, although the economic theory provided us with a general concept of the markets as a place or the field in which various economic activities are carried out and based on the idea of multiple types of markets according to the different degree of dominance of one of its parties, whether consumers or producers over price or quantities. Due to the peculiarity of the oil market and through this vision and analysis of market data in which the activities related to crude oil are practiced, the research topic came to analyze the reality of the oil market in its different directions
Keywords: for crude oil; monopoly; elasticity; demand